Correlation between leptin and LH concentration during peri and postpartum to the onset of estrus postpartum in Bali cattle - Laksmi, D. N. D. I; Trilaksana, I. G. N. B.; Sudimartini, L. M.; Gunawan, I. W. N. F. (Diponegoro University, 2020)
The mechanism of the hypothalamus, pituitary, and ovaria is important in the early postpartum luteal activity. This study aims to measure levels of the leptin hormone, Luteinizing Hormone (LH) during the first-time postpartum estrus appears and to observe the signs of estrus. The study uses a prospective observational method. The samples were Bali cattle on peripartum conditionwhile postpartum estrus appeared from several sistem pertanian terintegrasi (Simantri) in Mengwi District, Badung Regency, Bali, Indonesia. The measured parameters were leptin levels, LH, and the onset of postpartum estrus. The technique of measuring hormone levels with the Direct Elisa method and Double Antibody Sandwich. The results showed there were a positive correlation (r=0.773) between leptin levels at peripartum and the onset of postpartum estrus.The higher level of leptin, the faster of postpartum estrus appears. However, a minimum leptin value is needed to increase the LH level so that expression of estrus appearance is clearly.